Border economies of the Middle East: why do they matter for political economy?. Issue 3 (3rd May 2020) - Malik, Adeel; Gallien, Max
Abstract: Although borderland regions of the Middle East and North Africa represent active sights of economic and social exchange, they remain peripheral to the analysis of the region's political economy. Conventional accounts of cross-border informal trade tend to emphasize its illegality based on existing economic regulations, overlooking the deep political foundations of such trade. This article posits new arguments on the political economy significance of cross-border informal trade in the Middle East, highlighting its relevance for studying processes of state formation, durability of authoritarian regimes, conflict, informal institutions and the inter-dependence between domestic and external political economy domains. Our analysis underscores the need for a more holistic understanding of border economies that moves the field away from a security-centered view that treats such trade as mainly a law and order issue.